Seasonality in the Design of the Environment of a Hotel Facility on the Example of the Rest House for Employees of Lublin University of Technology in Kazimierz Dolny - Hołownia, Damian; Lisiewska, Dominika (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2024)
The authors analyse the impact of seasonality on the design of the environment of hotel facilities. As a case study, the Rest House for Employees of Lublin University of Technology in Kazimierz Dolny was chosen. The problem of variability of climatic conditions, and various forms of tourist activities, which require a flexible approach to design, allowing year-round use of space, is addressed. Both examples of space development in Poland and specific seasonal solutions for Kazimierz Dolny were discussed. An analysis of local conditions, including landscape values and cultural heritage of the city, was conducted. Proposals are presented for adapting the space around the rest house, taking into account the organization of spring and summer outdoor events, autumn cultural revival and winter recreational activities. Drawings of solutions for the recreational zones of the space around the Rest House of Lublin University of Technology are an integral part of the study. The article emphasizes that flexible space design can increase interest in the recreational facility and contribute to the development of the year-round offer of Kazimierz Dolny.